MILLIY HÁREKETLI OYİNLARDİŃ TÚRLERI HÁM TÁRBIYALİQ ÁHMIYETI - Shılmanov, R. (SCIENCE and SOCIETY, 2022)
In this article provides information about the national dances of the people of Karakalpakstan, with the help of the tradition to educate and use our youth in dexterity, speed, ingenuity, mobility, endurance, strength, nationality.